The patriarchal imagination: Emergence and silencing of the woman writer in the press and literature Ecuadorians, 1860-1900 - Astudillo-Figueroa, Alexandra (2024)
This work is an effort to bring together, based on the proposal of patriarchal domination, several research projects that demonstrate the author's interest in unraveling the patriarchal imagery that accompanied female writing and male literary criticism in Ecuador during the period from 1860 to 1900. Using literary articles and essays published in the press, novels, and unpublished documents as primary sources, it proposes a record of the emergence and silencing of women as writers in the press and as characters in Ecuadorian literature.